The Routledge Handbook of Chinese Translation - Shei, Chris; Gao, Zhao-Ming; Shei, Chris; Gao, Zhao-Ming (Taylor & Francis, 2017)
The Routledge Handbook of Chinese Translation presents expert and new research in analysing and solving translation problems centred on the Chinese language in translation. The Handbook includes both a review of and a distinctive approach to key themes in Chinese translation, such as translatability and equivalence, extraction of collocation, and translation from parallel and comparable corpora. In doing so, it undertakes to synthesise existing knowledge in Chinese translation, develops new frameworks for analysing Chinese translation problems, and explains translation theory appropriate to the Chinese context. The Routledge Handbook of Chinese Translation is an essential reference work for advanced undergraduate and postgraduate students and scholars actively researching in this area.
English
Keywords: Language teaching & learning (other than ELT); Press & journalism; Andy Lung Jan Chan|Arista Szu-Yu Kuo|Bai Liping|Binghan Zheng|Bonnie S. Mcdougall|Chung-Ling Shih|Chunshen Zhu|Dahui Dong|Daniel Tsung-Wen Hu|Darryl Sterk|Fan Shengyu|Huiling Ding|Jing Fang|John Minford|Jun Wen|Kefei Wang|Libo Huang|Liu Huawen|Mickey Wong|Miranda Lai|Nam Fung Chang|Nancy Xiuzhi Liu|Poon Wai Yee Emily|Sanjun Sun|Sheau-Harn Chiou|Sonya E. Pritzker|Szu-Wen Kung|Tan Zaixi|Ting Guo|Tong King Lee|Valerie Pellatt|Vincent Xian Wang|Xia Xiang|Xiaoli Li|Yashyuan Jin (Michael)|Yifeng Sun|Yong Zhong|Yukteshwar Kumar|Yvonne Lee|Yvonne Tsai|Zhao-Ming Gao|Zhongwei Song